2003
DOI: 10.1073/pnas.2033246100
|View full text |Cite
|
Sign up to set email alerts
|

Widespread cytoplasmic mRNA transport in yeast: Identification of 22 bud-localized transcripts using DNA microarray analysis

Abstract: Cytoplasmic mRNA localization provides a means of generating cell asymmetry and segregating protein activity. Previous studies have identified two mRNAs that localize to the bud tips of the yeast Saccharomyces cerevisiae. To identify additional localized mRNAs, we immunoprecipitated the RNA transport components She2p, She3p, and Myo4p and performed DNA microarray analysis of their associated RNAs. A secondary screen, using a GFP-tagged RNA reporter assay, identified 22 mRNAs that are localized to bud tips. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
319
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(345 citation statements)
references
References 54 publications
15
319
0
Order By: Relevance
“…Ten of these RNAs were transcribed from cell cycle-regulated genes, whereas others appeared to participate in pathways related to sensing or responding to stress. The overlap between these previous studies and ours is high: we identified 41 mRNAs that co-isolated with She2p-PrA, including 90% and 65% of the transcripts previously identified, respectively 29,30 (Table 2 and Supplementary Table 3). Our results also suggest that the number of transcripts associated with She2p alone is greater than previously reported.…”
Section: Global Analyses Of Nop15p and She2p Associated Rnasmentioning
confidence: 61%
See 2 more Smart Citations
“…Ten of these RNAs were transcribed from cell cycle-regulated genes, whereas others appeared to participate in pathways related to sensing or responding to stress. The overlap between these previous studies and ours is high: we identified 41 mRNAs that co-isolated with She2p-PrA, including 90% and 65% of the transcripts previously identified, respectively 29,30 (Table 2 and Supplementary Table 3). Our results also suggest that the number of transcripts associated with She2p alone is greater than previously reported.…”
Section: Global Analyses Of Nop15p and She2p Associated Rnasmentioning
confidence: 61%
“…Our She2p RNP complex isolations form an excellent positive control, as in two recent microarray studies, 11 and 24 transcripts, respectively, were reported to be specifically associated with tagged trimeric She2p-She3p-Myo4p complexes 29,30 . Ten of these RNAs were transcribed from cell cycle-regulated genes, whereas others appeared to participate in pathways related to sensing or responding to stress.…”
Section: Global Analyses Of Nop15p and She2p Associated Rnasmentioning
confidence: 91%
See 1 more Smart Citation
“…It has been reported that many mRNAs and RNA-binding proteins are localized to specific compartments, along with cytoskeletal elements, in a variety of eukaryotic cells (Jansen, 2001;Kloc et al, 2002). In S. cerevisiae, many mRNAs are localized to produce proteins in specific compartments such as the daughter cell or the mitochondria (Corral-Debrinski et al, 2000;Takizawa et al, 2000;Jansen, 2001;Kwon and Schnapp, 2001;Shepard et al, 2003). These observations suggest that individual mRNAs may be consistently transported to specific areas in the yeast cell.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, the cortical ER is moved by Myo4p, the other yeast myosin-V, which forms a complex with She3p (Estrada et al, 2003). Several mRNAs are also moved by Myo4p and require both She3p and She2p, proteins whose roles are not well established (Bohl et al, 2000;Long et al, 2000;Shepard et al, 2003;Heuck et al, 2007;Hodges et al, 2008). Moreover, rather than attachment to the globular tail, She3p binds the rod of Myo4p.…”
Section: Introductionmentioning
confidence: 99%